2021
DOI: 10.1111/evo.14265
|View full text |Cite
|
Sign up to set email alerts
|

Testing the adaptive value of sporulation in budding yeast using experimental evolution

Abstract: Load file and massage the well namesLoad previously run stan model output load("FittedModels.RData") load("AncModels.RData")

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Higher frequencies of admixed isolates observed in fruits may simply be a result of increased contacts with other lineages. Alternatively, fruits and organisms associated with those fruits such as frugivorous animals and vectors may represent niches that promote hybridization; for instance, sporulation has been suggested to be an adaptation that allows cells to survive in nutrient-depleted conditions such as insects' intestines during experimental passaging (Thomasson et al 2021). Notably, the presence of CHN-VI/VII.2 genetic components in many natural lineages across the world, as well as in admixed isolates found in fruits, raises the possibility that the common ancestors dispersed from East Asia were from this lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Higher frequencies of admixed isolates observed in fruits may simply be a result of increased contacts with other lineages. Alternatively, fruits and organisms associated with those fruits such as frugivorous animals and vectors may represent niches that promote hybridization; for instance, sporulation has been suggested to be an adaptation that allows cells to survive in nutrient-depleted conditions such as insects' intestines during experimental passaging (Thomasson et al 2021). Notably, the presence of CHN-VI/VII.2 genetic components in many natural lineages across the world, as well as in admixed isolates found in fruits, raises the possibility that the common ancestors dispersed from East Asia were from this lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast sporulation tends to be triggered by chemical conditions that correlate with depletion of sugars and crowding of yeast (Neiman, 2005). Natural yeast isolates do vary in their propensity to sporulate (Liti et al, 2009), and vary in their ability to evolve increased sporulation rates (Thomasson et al, 2021). Less is known about how sporulation proceeds under natural conditions and to what extent sporulation represents a facultative program.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, enhanced sporulation in killer yeast may be an adaptation to predation. Thomasson et al (2021) demonstrated that sporulation is an adaptive trait, and that insect passaging selects for yeasts with higher rates of spore production. Drosophila attraction varies across yeast strains (Buser et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This would suggest that predation by insects has influenced their evolution (Thomasson et al, 2021).…”
mentioning
confidence: 99%